Features of the deep structure of the sites of the location of world-famous religious complexes, the resort center in Truskavets and the ancient settlement of Arkaim - Yakymchuk, M.A.; Korchagin, I.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
The results of a reconnaissance survey of the areas of famous religious (cult) complexes, as well as the territory of the resort center in Truskavets and the site with the ancient settlement “Arkaim” are presented. Experiments with using direct prospecting technology of frequency-resonance processing and interpretation of satellite images and photographs were carried out in order to study the features of the deep structure in the survey areas. Religious buildings of the surveyed areas of Pochaev, Kiev-Pechersk and Sergieva Lavra are located in the contours of basalt volcanic complexes, through which hydrogen migrates to the upper horizons of the cross-section and, further, into the atmosphere. In the upper part of the cross-section, including at a shallow depth, the presence of reservoirs with living (healing) water and hydrogen have established by instrumental measurements. The conducted studies confirmed the facts of hydrogen migration into the atmosphere. The resort center in Truskavets and the area of the ancient Arkaim settlement location are also located within basalt volcanoes, on which signals are recorded at the frequencies of hydrogen, red phosphorus, living water, and the instrumental measurements confirm the migration of hydrogen into the atmosphere. In the resort center, in the upper part of the cross-section above the basalts, accumulations of hydrogen can be found in a reservoir of 84 m thick, which is overlain by metamorphic rocks of the gneiss group. The results of the experimental work carried out are important arguments in favor of the “volcanic” model of the formation of various structural elements of the Earth, as well as deposits of combustible and ore minerals (including hydrogen and water). During the research, additional facts (evidence) were also obtained in favor of the deep (abiogenic) genesis of oil, condensate, gas and water in the process of hydrogen degassing of the Earth. Research materials indicate the feasibility of using mobile technology of frequency resonance processing and decoding of satellite images and photographs to study the deep structure of survey objects, detect and localize oil and gas promising areas and hydrogen accumulation zones in areas of basalt volcano’s location, as well as in areas of hydrogen degassing. The use of super-efficient and low-cost directprospecting technology will significantly speed up the exploration process for hydrogen, oil, condensate and gas, as well as reduce financial costs for its implementation.